2016
DOI: 10.1186/s12929-016-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of amphetamine-induced sensitization: HDAC5 expression and microRNA in neural remodeling

Abstract: BackgroundHistone deacetylase (HDAC) activities modify chromatin structure and play a role in learning and memory during developmental processes. Studies of adult mice suggest HDACs are involved in neural network remodeling in brain repair, but its function in drug addiction is less understood. We aimed to examine in vivo HDAC5 expression in a preclinical model of amphetamine-induced sensitization (AIS) of behavior. We generated specific contrast agents to measure HDAC5 levels by in vivo molecular contrast-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The second most highly expressed miRNA in human milk EVs, miR-3197, has been suggested to be semen-specific in forensic studies 53,54 , however, miR-3197 expression was detected in human mesenchymal stem cells 55 , human placenta 56 , serum from patients with hepatocellular carcinoma 57 . miR-1286 is a putative HDAC5 (histone deacetylase 5) repressor, which in turn regulates RUNX2 (Runt-Related Transcription Factor 2), and playing a role in osteogenesis and osteoporosis [58][59][60] . We examined correlations between highly expressed miRNAs in our population to determine which miR-NAs may be co-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The second most highly expressed miRNA in human milk EVs, miR-3197, has been suggested to be semen-specific in forensic studies 53,54 , however, miR-3197 expression was detected in human mesenchymal stem cells 55 , human placenta 56 , serum from patients with hepatocellular carcinoma 57 . miR-1286 is a putative HDAC5 (histone deacetylase 5) repressor, which in turn regulates RUNX2 (Runt-Related Transcription Factor 2), and playing a role in osteogenesis and osteoporosis [58][59][60] . We examined correlations between highly expressed miRNAs in our population to determine which miR-NAs may be co-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is in a very early stage, this technology was found to be more efficient and cost-effective, and it may be expanded for broader proteomics and metabolomics applications. With a similar approach, Liu et al functionalized the SPION with HDAC5- and miRNA-specific labeling to detect the levels of HDAC5 mRNA in vivo using contrast-enhanced (MCE)–MRI [46], demonstrating a novel application in epigenetics. More recently, several studies have indicated a possible application of IONP formulations in anticancer treatments [3840, 4749].…”
Section: General Overview and Biomedical Application Of Iron-basedmentioning
confidence: 99%
“…Chronic administration of d‐amph was able to increase HDAC activity in hippocampus and striatum but not in frontal cortex. Other studies demonstrated that chronic administration of amphetamine was able to increase HDAC activity in the frontal cortex of rats (Stertz et al., 2014) and HDAC5 expression in the lateral septum and the striatum of mice (Liu & Liu, 2016). As expected, VPA and SB treatment decreased HDAC activity in both saline‐ and d‐amph‐treated animals compared to the control group—except frontal cortex and striatum, where VPA had no effect and lower effect, respectively.…”
Section: Discussionmentioning
confidence: 96%